Children’s calendar folklore of Tuvinians - Kara-ool, Chinchi A. (The New Research of Tuva, 2015)
This article is devoted of children’s calendar folklore culture of Tuvinians as zaklichki. The author reveals peculiar features of this genre its importance in traditional culture of Tuvinians.
Keywords: children’s folklore; children’s calendar folklore of tuvinians; zaklichki